The predictive power of environmental concern, perceived behavioral control and social norms in shaping pro-environmental intentions: a multicountry study - Kotyza, Pavel; Cabelkova, Inna; Pierański, Bartłomiej; Malec, Karel; Borusiak, Barbara; Smutka, Luboš; Nagy, Sandor; Gawel, Aleksandra; Bernardo López Lluch, David; Kis, Krisztián; Gál, József; Gálová, Jana; et al. (Frontiers in Ecology and Evolution, 2024)
Pro-environmental intentions encourage individuals to make conscious decisions that help protect the environment, reduce waste, conserve resources, and preserve natural habitats. This study aims to assess the predictive power of environmental concern, perceived behavioral control and social norms in determining the pro-environmental intentions in the Theory of Planned Behavior (TPB) framework. Methodologically we rely on Structural Equation Modelling (SEM), applied to the survey study among 2,702 university students majoring in economics, finance, management, or marketing from Croatia, the Czech Republic, Hungary, Poland, Slovakia, and Spain. The results show that the model explained 51% of the total variance of pro-environmental intentions, with the predictive power of environmental concern and perceived behavioral control at 42% and 45%, respectively, and social norms at only 6% (out of total 51% of explanatory power). The implications of our results suggest a major focus on increasing environmental concern and perceived behavioral control in behavioral interventions to support pro-environmental behavior. The effectiveness of social pressure produced by injunctive social norms proved limited. The cross-country differences were not statistically significant. More research must be done to study the relative effect of injunctive and descriptive social norms on proenvironmental behavior.